Impact of adding preoperative magnetic resonance imaging to ultrasonography on male breast cancer survival: a matched analysis with female breast cancer - Jeongmin Lee; Ka Eun Kim; Myoung Kyoung Kim; Haejung Kim; Eun Sook Ko; Eun Young Ko; Boo-Kyung Han; Ji Soo Choi (Ultrasonography)
Purpose The study investigated whether incorporating magnetic resonance imaging (MRI) alongside ultrasonography (US) in the preoperative evaluation is associated with differing survival outcomes between male and female breast cancer patients in a matched analysis. Additionally, clinicopathological prognostic factors were analyzed. Methods Between January 2005 and December 2020, 93 male and 28,191 female patients who underwent breast surgery were screened. Exact matching analysis was conducted for age, pathologic T and N stages, and molecular subtypes. The clinicopathological characteristics and preoperative imaging methods of the matched cohorts were reviewed. Disease-free survival (DFS) and overall survival (OS) were assessed using Kaplan-Meier analysis, and Cox proportional hazards regression analysis was used to identify prognostic factors. Results A total of 328 breast cancer patients (61 men and 267 women) were included in the matched analysis. Male patients had worse DFS (10-year DFS, 70.6% vs. 89.2%; P=0.001) and OS (10-year OS, 64.4% vs. 96.3%; P<0.001) than female patients. The pathologic index cancer size (hazard ratio [HR], 2.013; 95% confidence interval [CI], 1.063 to 3.810; P=0.032) was associated with worse DFS, whereas there were no significant factors associated with OS. Adding MRI to US for preoperative evaluation was not associated with DFS (HR, 1.117; 95% CI, 0.223 to 5.583; P=0.893) or OS (HR, 1.529; 95% CI, 0.300 to 7.781; P=0.609) in male patients. Conclusion Adding breast MRI to US in the preoperative evaluation was not associated with survival outcomes in male breast cancer patients, and the pathologic index cancer size was associated with worse DFS.